Research network on irrigation management for diversified cropping in rice-based systems. proceedings of the Organizational and Planning Workshop held at the Asian Institute of Technology Bangkok, Thailand, 30 November- 3 December 1988 - International Irrigation Management Institute (International Irrigation Management Institute, 1989)
This book constitutes the proceedings of an organizational and planning workshop for a research network on irrigation management for diversified cropping in rice-based system held in late 1988 in Bangkok. The workshop participants agreed to establish research network involving eight humid Tropical Asian countries in which irrigated rice is the main crop during the wet season.